2016
DOI: 10.1182/bloodadvances.2016000497
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils and the S100A9 protein critically regulate granuloma formation

Abstract: Key Points• S100A91 neutrophils accumulated prominently in the central area of granulomas in humans and guinea pigs.• Granuloma formation was markedly impaired by a treatment with the S100A9 inhibitor, tasquinimod. antigen as S100A9, a calcium-binding protein of the S100 family, which was expressed abundantly in neutrophils. Consistent with the multifaceted functions attributed to S100A9, including its role in neutrophil extravasation and macrophage activation, the blockade of S100A9 functions with the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 48 publications
1
20
0
1
Order By: Relevance
“…S100A9 proteins were specifically accumulated in the caseum of both TB and MAC-LD. This result is consistent with a previous report that S100A9 accumulated in the caseum of TB granulomas (Yoshioka et al, 2016). Proteins mainly expressed in neutrophils, including S100A9, were accumulated in the caseous sub-compartments of TB and MAC-LD granulomas, suggesting that neutrophils infiltrate into the caseum, and exacerbate pathogenesis (Dallenga and Schaible, 2016;Remot et al, 2019).…”
Section: Detection Of Mycobacterial Proteins In Granulomatous Lesionssupporting
confidence: 93%
“…S100A9 proteins were specifically accumulated in the caseum of both TB and MAC-LD. This result is consistent with a previous report that S100A9 accumulated in the caseum of TB granulomas (Yoshioka et al, 2016). Proteins mainly expressed in neutrophils, including S100A9, were accumulated in the caseous sub-compartments of TB and MAC-LD granulomas, suggesting that neutrophils infiltrate into the caseum, and exacerbate pathogenesis (Dallenga and Schaible, 2016;Remot et al, 2019).…”
Section: Detection Of Mycobacterial Proteins In Granulomatous Lesionssupporting
confidence: 93%
“…soluble mediators, thereby disrupting the immunosuppressive tumor microenvironment (4-6). Moreover, it was recently shown that granuloma formation was markedly impaired by TSQ treatment in a guinea pig model (7). We recently demonstrated that denileukin diftitox, a recombinant protein toxin targeting CD25 1 cells, restricted bacterial replication and depleted suppressor cells in TB-infected organs (8).…”
Section: Resultsmentioning
confidence: 99%
“…Meningitic E. coli and nicotine can additively or synergistically induce the cellular release of Ca 2+ which may expand bacterial cell signaling through the cholinergic α7R pathway (Chi et al, 2011). S100A9 is expressed abundantly in neutrophils and is able to regulate the ability of neutrophils to respond acutely to infection (Raquil et al, 2008;De Filippo et al, 2014;Yoshioka et al, 2016). The presence of S100A9 is critical in both murine and human NETs to inhibit bacterial growth (Achouiti et al, 2012).…”
Section: Discussionmentioning
confidence: 99%